Optimization of preventive maintenance on critical machines at the Sabiz 1 plant using Reliability-Centered Maintenance method - Cahyati, Sally; Puspa, Sofia Debi; Himawan, Riswanda; Agtirey, Novan Rojabil; Leo, Joseph Andrew (SINERGI, 2024)
Maintenance planning is the first step in an industry, especially when it comes to the trade-off between cost and reliability, which is the reason for this research's aim. The Reliability Centered Maintenance (RCM) method will be used in this research to optimize maintenance activity in critical machines at the Sabiz 1 plant to minimize downtime, costs incurred for machine repairs, and production losses. The tools of RCM that will be used such as FMEA to determine critical machines as the focus of analysis, a Fishbone Diagram to determine the causes of failure, an RCM worksheet to get preventive activities, and a statistical distribution approach to obtain appropriate preventive activity intervals. The result of data processing shows that all data has a lognormal distribution and can be continued using the lognormal distribution method. The results of this analysis are the preventive maintenance activities proposal and their intervals as a reference for Sabiz 1 plant maintenance planning. The preventive maintenance plan for three critical machines is the high-pressure pump is four days of inspection activities and two days for replacement activities; for the powder, base conveyor is four days of checking activities and 17 days for replacement activities; and for the extraction tower fan for inspection, activities is seven days. The prediction of the implementation impact of this maintenance planning will save maintenance costs around 70% compared to historical costs.